KOPERASI SEKTOR RIIL DI KOTA JAMBI: TINJAUAN UPAYA OPTIMALISASI DAN FAKTOR PENGHAMBAT - Nisya Puspita Safitri (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
Real sector cooperatives are one of the potentials of the local economy. Of the 220 cooperatives in Jambi City, only 34 are based in the real sector. This is despite the fact that the real sector plays a crucial role in regional development. This article aims to analyze the development of real sector cooperatives in Jambi City through a review of the opportunities and challenges faced by cooperatives. This study uses a qualitative descriptive approach. The data used are secondary data related to real sector cooperatives. The data collection technique used is a literature study. Data analysis was conducted using descriptive methods. The results show that the challenges faced by real sector cooperatives in Jambi City are in the aspects of capital, low member participation, cooperative management, product aspects, financial management aspects, and the use of digital media. Meanwhile, opportunities include establishing cooperatives based on primary health services, real sector cooperatives engaged in food, agribusiness, and community-based tourism in the village. In addition, the establishment of the Red and White cooperative by the government is an effort to optimize real sector cooperatives as an effort to empower communities and equalize welfare